A Robust Mobile-Based Incident Reporting System - Opoku, Samuel King; Mohammed, Humu (IJRDO -Journal of Computer Science Engineering, 2017)
With the rampant occurrences of crime, societies have various methods for alerting the police whena crime strikes. Currently in many countries, report to the police occurs after the crime. The reporters are askedto make full statement that includes everything they can remember about the incident. The police then embarkon investigation and they may or may not arrest the victim. In well-established organizations, buttons areinstalled which are pressed to notify the police in case of emergency. However, the buttons may be at fardistance to be pressed during the incident. The use of a mobile phone is not limited to talking alone it is beingused in making video, recording information and transmitting it to a phone or a computer as was being done bya computer. This paper develops an incident reporting system that uses mobile phone and wirelesscommunication technology. The user at the crime screen long presses a key and a message from the client’sphone is sent to the receiving phone be a police system or guardian system stating the location of the user. Thepaper also analyses the various wireless communication technology used in mobile communication technologydetermining their pros and cons